Features of international conflicts in modern world (Journal of Philosophy Culture and Political Science, 2019)
In given article the main factors and features of modern international confl icts are analyzed. Also, the reasons and forms ofinternational confl icts of modern world are revealed. Authors defi ned an essence and character of international confl icts and theirconsequences were analyzed. Due to the change of characteristics and essence of international confl icts different ways of regulation andtheir decision were considered.